The onset of fretting at the head‐stem connection in hip arthroplasty is affected by head material and trunnion design under simulated corrosion conditions. Issue 6 (10th January 2018) - Rowan, Fiachra E.; Wach, Amanda; Wright, Timothy M.; Padgett, Douglas E.
ABSTRACT: Mechanically assisted crevice corrosion (MACC) is a mechanism for trunnion damage in total hip arthroplasties (THAs). Retrieval studies have shown reduced MACC‐related damage for ceramic heads compared with cobalt–chromium (CoCr) heads. We propose that ceramic heads demonstrate fretting at higher cyclic compressive loads than CoCr heads on titanium alloy trunnions in a simulated corrosion model. A closed electrochemical chamber was used to measure fretting current onset loads for two modern titanium alloy trunnions (Zimmer 12/14 and Stryker V‐40) in which trunnion failure has been reported. Ceramic and CoCr alloy 36 + 0 mm heads were impacted on each trunnion and cyclically loaded at 3 Hz with increasing magnitude from 100 to 3, 400 N for 540 cycles. Onset load was the cyclic compressive load at which the slope of the average fretting current increased significantly. A CoCr head with V40 trunnion demonstrated the lowest onset load (1, 400 N), while the V40 trunnion with a ceramic head showed the highest onset load (2, 200 N). Significant differences occurred in average fretting current between head materials for V40 trunnions ( p < 0.001) at loads over 2, 000 N. CoCr‐12/14 and ceramic‐12/14 couples demonstrated similar onset loads (2, 000 N). All head–trunnion combinations showed cyclical fretting response to loading at 100 N. Head material composition was observed to increase fretting at the taper junction but the effect was taper geometry dependent. Using ceramic heads may reduce the phenomena of trunnion fretting and corrosion but the effect of both trunnion geometry and metallurgy warrants further investigation. Statement of clinical significance: Trunnion corrosion may occur with titanium alloy stems regardless of the head material used. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1630–1636, 2018. Abstract : A closed electrochemical chamber was used to measure fretting current onset loads for two titanium alloy trunnions in which trunnion failure has been reported. A CoCr head with V40 trunnion demonstrated lowest onset load (1, 400 N), while the V40 trunnion with a ceramic head showed the highest onset load (2, 200 N). Average fretting current between head materials for V40 trunnions were differenct at loads over 2, 000 N ( p < 0.001). CoCr‐12/14 and ceramic‐12/14 couples demonstrated similar onset loads (2, 000 N).